Collection Development Variables and Utilization of Information Resources in University Libraries, South-South, Nigeria - Patience Owere EKPANG; William Ofem. NKANU (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
This study investigated the relationship between collection development variables, and utilization of information resources in university libraries, south-south, Nigeria. To achieve the purpose of this study, two research questions were raised and two hypotheses were formulated to guide the study. Ex-post facto research design was adopted for the study. The population of the study was 16620 students and a sample of 800 respondents was awareness for the study. The awareness was done through the stratified and purposive random sampling technique. The results of the analyses revealed a significant relationship between awareness, acquisition and utilization of information resources. Based on these findings, it was recommended, among others that: Government should prioritize funding for the acquisition of information resources for university libraries